Toward systematization of organization theory of the XX century - Biljana Bogićević - Milikić (Anali Ekonomskog fakulteta u Subotici, 2020)
Organization theory of the XX century is characterized by tremendous fragmentation and complexity. Until now there have been several attempts, although not generally accepted, to classify all theories and to pro-duce a single typology which would smooth out understanding of phenomena within and around organizations. In this paper we analyzed the classifications which gained huge popularity among scholars and made an effort to develop an integral framework for systematization of organization theory of the XX century.